Aplikasi Monitoring Aset dan Inventaris Laboratorium Berbasis Web Pada Kampus Politeknik Negeri Ujung Pandang - Parenreng, Mardawia Mabe; Nas, Mardhiyah (Politeknik Negeri Ujung Pandang, 2019)
Polytechnic is a university that organizesvocational education in various science and technology clusters.The learning process in polytechnic is dominated by practicumthat is 70% and 30% theory. The amount of laboratorypercentage affects the large number of laboratory. Eachlaboratory has a laboratory responsible (technician) in charge ofrecording and monitoring the completeness and condition of thepracticum equipment. Tools and materials used in the process ofpracticum is an asset and laboratory inventory that must alwaysbe maintained and checked the condition of the equipment. InUjung Pandang State Polytechnic (PNUP) in terms of assetmonitoring and practicum inventory is still done manually.Therefore need to make an application to monitor assets andlaboratory inventory, especially on campus two. It is known thatsince 2014 there are three departments that have implementedthe teaching and learning process in two campuses includingseveral laboratories have also been transferred to the twocampuses, such as electrical engineering majors, majoring inbusiness administration and accounting majors. So with thisapplication will greatly help technicians because no longer do thereporting or request tool manually and with this application inmonitoring the condition of the tool is damaged and tools thatneed further improvement more easily and can be quicklyupdated. The creation of this system begins with the needsanalysis, design design as the basis of system development, theright of access consists of technicians of each laboratory andprocurement department on campus one, content creationconsists of laboratory data, checking tools and materials, repairtools and materials and demand tools and materials then printdata laboratory